Design, simulation analysis and fabrication of the conceptual innovative hand tool for Tuber Harvester - Abdul Ssomad Bin M Abd Halim
Dioscorea hispida (D.hispida) is a poisonous plant normally found in wildlife forest where scientific studie have shown that its tuber contains toxic poison and can be consumed after its poison is removed. On the other hand, harvesting the tuber of D. hispida is time consuming and difficult due to the existing hand tool is heavy and required a large force to harvest the tubers. Therefore, the essential development of an innovative hand tool harvest is required to improve and facilitate the harvesting process. Using digital gauge, tuber extraction force was measured in order to be fed into the Computer Aided Design (CAD) simulation. Three designs of hand tools (straight, bnt and fulcrum) were proposed and the design selection was based on the lowest displacement and stress value. This was done using SolidWorks CAD software. Further analysis was conducted to select the best material for the selected design based on stress analysis and factor of safety. The result from field experiments showed that the bent type hand tool required less force to extract the D.hispida in comparison to the traditional hoe. A force reduction at approximately of 10% was achieved by the newly proposed design as well as fabrication from material which is lighter and stronger.